Cross-sectional online survey of the impact of new tobacco health warnings in Colombia - Sally Adams; Arturo Clavijo; Ricardo Tamayo; Olivia Maynard (BMJ Open)
Objectives This study aimed to explore the impact of a new set of six pictorial warnings introduced in 2018.Design and setting Using a cross-sectional design, we examined awareness of the new warnings among Colombian smokers across two time points of data collection.Participants Adult smokers (≥18 years of age), defined as having smoked at least 100 cigarettes in their lifetime and currently smoking at least one cigarette per week participated at time 1, prior to the introduction of the new health warnings in Colombia in 2018 (n=1985, 72% male), and at time 2, 12 months post introduction (n=1572, 69% male).Primary outcomes At each time, we examined smokers’ responses to warnings on packs (negative affect, thinking about warning messages and cognitive elaboration), attitudes toward smoking (perceived likelihood and severity of harm, self-efficacy, response efficacy and quit intentions), knowledge of the health risks of smoking and responses to the new warnings (negative affect, believability, thinking about the harms, reactance and perceived message effectiveness).Results Awareness of the warnings was low, with only 59% of smokers reporting having seen them at time 2. Between times, we observed a reduction in negative affect toward current warnings (p<0.001), reduced thinking about (p<0.001) and cognitive elaboration of the warning message (p<0.001), and an increase in perceived severity of warnings (p<0.001). When asked about the six new health warnings, we found a reduction in negative affect (p<0.07), cognitions related to harm (p<0.01), believability (p<0.03), reactance (p<0.01) and perceived message effectiveness (p<0.02) between times.Conclusions Our data indicate that effectiveness was low prior to the introduction of the new health warnings and at 12 months post introduction. Tobacco control policy should seek to improve exposure to and noticeability of tobacco health warnings in Colombia.